2012
DOI: 10.1103/physreva.85.053806
|View full text |Cite
|
Sign up to set email alerts
|

Strong magnetic coupling of an inhomogeneous nitrogen-vacancy ensemble to a cavity

Abstract: We study experimentally and theoretically a dense ensemble of negatively charged nitrogenvacancy centers in diamond coupled to a high Q superconducting coplanar waveguide cavity mode at low temperature. The nitrogen-vacancy centers are modeled as effective spin one defects with inhomogeneous frequency distribution. For a large enough ensemble the effective magnetic coupling of the collective spin dominates the mode losses and inhomogeneous broadening of the ensemble and the system exhibits well resolved normal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(105 citation statements)
references
References 25 publications
3
101
1
Order By: Relevance
“…To investigate the temperature dependence of the collective coupling strength to each mode, we measure transmission spectra at several temperatures in the range 0.25-1.2 K and perform the same analysis as above [14,15,25]. The results are shown in Fig.…”
mentioning
confidence: 99%
“…To investigate the temperature dependence of the collective coupling strength to each mode, we measure transmission spectra at several temperatures in the range 0.25-1.2 K and perform the same analysis as above [14,15,25]. The results are shown in Fig.…”
mentioning
confidence: 99%
“…In the system, the coupling strength between an NVE and a TLR can be enhanced to about 10 ∼ 65 MHz [47,49], and the NVE can act as either a qubit or a good memory because the coherence time of an NV-center is much longer than that of an SPQ [46].…”
Section: Discussion and Summarymentioning
confidence: 99%
“…For example, in 2010, Kubo and coworkers [47] realized the strong coupling of a spin ensemble, which is composed of NV-centers in a diamond crystal, to a superconducting resonator. In 2012, Sandner et al [49] showed that a dense NVE can be coupled to a high-Q superconducting resonator at low temperature both in experiment and in theory. In 2011, Kubo et al [50] reported the experimental realization of a hybrid quantum circuit combining a superconducting transmon qubit and an NVE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1/2 [33], which leads to the enhancement of a single coupling strength, g j , by a factor of √ N (N ≈ 10 12 in [29]). We are aiming at the transfer of information from the cavity to the spin ensemble, its storage over a well-defined period of time, and its transfer back to the cavity.…”
Section: Theoretical Modelmentioning
confidence: 99%